Solid State Structural, Catalytic and Physico-chemical Elucidation of VO(IV), Pt(IV) and Ce(IV) Coordinated Compounds of Schiff Bases - Gaur, S.; Choudhary, J.; Purohit, R. (Asian Journal of Chemistry, 2010)
Pt(IV), VO(IV) and Ce(IV)-complexes of the Schiff bases, viz., 2-(phenylthio) anilimino-4- chloro benzylidene (PACB), 2-(phenylthio) anilimino-4-chloro-3-nitro benzylidene (PACNB) and 2-(phenylthio) aniliamino-4-methoxy benzylidene (PAMB) have been synthesized and characterized by elemental analyses, molar conductance, electronic, infrared spectra, 1H NMR, ESR, thermal and magnetic susceptibility measurements. Synthesized complexes have been tested for their reactivity and substitution behaviour. All the ligands behave as bidentate, coordinating through O and N atoms. The proposed geometry for the complexes is square-pyramidal. Conductivity studies reflect the semi-conducting behaviour of the complexes.